(untitled) (Medico Legal Update, 2021)
Background: Wart is common disease cause by infection with HPV, there are many modalities for treatment most of them resolve wart with many side effects as scars and recurrence. Objective: To identify the significant difference between two doses of intralesional vitamin D3 (60,000 vs 120,000) iu injection in treatment of warts. Patients and Method: A total of 47 patients were included in the study divided into two groups. Group A received intralesional 60,000 iu of vt.D3, and group B received intralesional 120,000 iu vt. D3 into each lesion with maximum of five warts treated in one session. Four sessions was done every 2 weeks in both groups. Follow-up was done for 4 months after last session of treatment for any recurrence. Results: In group A: complete response in 77.7%, partial response in 6.67%, minimal response in 6.67%, and no response in 6.67% of patients. About 60% of patients with multiple warts showed complete clearance of distant untreated warts. In group B: complete response in 66.7%, partial response in 6.67%, minimal response in 20%, and no response in 6.67% of patients. There was no significant difference between both groups. No recurrence was observed in both groups in the follow-up period. Conclusions: Immunotherapy by both intralesional MMR vaccine and vitamin D3 is simple, well-tolerated, and effective.